The use of instructional media in the excretory system: a study on the perspectives of teachers and eleventh grade students of senior high school - Safira Permata Dewi; Lutfiah Anggraini; Masagus Muhammad Tibrani (Universitas Negeri Jakarta, 2023)
Selection of learning media can affect the learning process that takes place in class. In addition, teachers are required to have the ability to use instructional media. This study aims to find out the types of learning media and how teachers get the learning media used in excretion system material. This survey research involved class XI students of public and private high schools in Palembang City, Indonesia. Samples of students were taken using the Stratified Cluster Random Sampling technique based on Accreditation A (266), Accreditation B (80) and Accreditation C (25) (n = 371) from 11 high schools in Palembang City. The sample of teachers was taken from the schools that were sampled in this study (Accreditation A 10 teachers, Accreditation B 3 teachers and Accreditation C 1 teacher) (n=14). The instrument used in this study was a questionnaire sheet for students and teachers. Questionnaire sheets were developed by taking into account learning indicators. The results of the student questionnaire showed that students were more interested in audio-visual and visual media. The audio-visual media that students like is learning videos, while the visual media that is preferred is the use of real objects and artificial objects. Meanwhile, the learning media most often used by teachers are audio-visual media and visual media. Students give a positive response to the media used by the teacher, even though the teacher does not develop the learning media himself. The results of this study are expected to assist teachers in choosing suitable learning media for use in biology lessons on excretory system material.